Student Perceptions of the Ethics of Using Artificial Intelligence in Academic Activities at Universities - Khojanatun, Khojanatun (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2026)
The emergence of generative artificial intelligence (AI), particularly ChatGPT, has fundamentally transformed higher education and given rise to various ethical challenges that cannot be ignored, especially those related to academic integrity and the formation of professional character. This study aims to analyze how students perceive the ethics of AI use in academic activities, focusing on three main dimensions: integrity, transparency, and professional responsibility. The approach used is descriptive quantitative, employing a questionnaire instrument with a 5-point Likert scale, involving 178 students of Institut Prima Bangsa as respondents selected through purposive sampling. Data analysis was conducted using descriptive statistics as well as validity and reliability tests with the assistance of SPSS software. The theoretical framework underpinning this study includes the Technology Acceptance Model (TAM), the Theory of Planned Behavior (TPB), and the AI ethics frameworks from UNESCO (2021) and NIST (2023). The results show that, overall, students’ perceptions of the ethics of AI use fall into the high category, with a mean score of 3.64. A total of 88.8% of students expressed their support for the establishment of formal policies regarding the use of AI at their institution. Furthermore, a weak but significant positive relationship was found between how frequently students use AI and their level of ethical awareness (rs = 0.312; p = 0.001). This study is expected to make a tangible contribution to the formulation of responsible AI governance policies in higher education that are grounded in the ethical values of the profession.